Legitimacy, Meaning and Knowledge in the Making of Taiwanese Identity - Harrison, M. author. aut Link
IX, 254 p.
Keywords: Harrison offers a new, critical approach to understanding the formation of Taiwan's identity. It applies contemporary social theory and historiography to a wealth of detail on Taiwanese politics, culture and society.